Large deviations for Bayes discrimination of a finite number of simple hypotheses - Gabriel', L. A.; Lin'kov, Yu. N. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider the problem of discrimination of a finite number of simple hypotheses in the general scheme of statistical experiments. Under conditions of the validity of theorems on large deviations for the logarithm of likelihood ratio, we investigate the asymptotic behavior of probabilities of errors of the Bayes criterion. We obtain the asymptotics of the amount of Shannon information contained in an observation and in the Bayes criterion.